Can a change in protocol increase rates of vaginal birth after caesarean?. (16th November 2010) - McCloud, K; Pierce, SJ; McCormack, J
Abstract : Patients with a single previous Caesarean section for non-recurrent cause can have a successful vaginal delivery in >75% cases.1 Elective Caesarean with no medical indication is associated with increased maternal mortality and severe morbidity.2 Uptake of vaginal birth after Caesarean (VBAC) however is dependent on many factors including, maternal perception and choice. Can the authors increase uptake of VBAC in this patient group? Method: Patient suitability for VBAC determined by senior obstetrician at 20 weeks, Caesarean for non medical reason only permitted with two consultant's agreement. Those who did not labour by 41 weeks had cervical assessment – if ARM (artificial rupture of membrane) was feasible, labour was induced; if not Caesarean section performed. Data Collection: Retrospective analysis of all patients with single previous Caesarean. Delivery outcomes and maternal and fetal morbidity assessed 6 months pre- and postprotocol change. Results: 59% (94/159) had trial of labour (control 46%), of which 77% (72/159) had successful vaginal delivery (control 62%). Spontaneous labour occurred in the majority. 11% were induced with 80% of inductions achieving vaginal birth. 65/159 (41%) had elective Caesarean section (control 54%). There were no cases of uterine rupture or perinatal death. A significant difference (p<0.05%) in estimated blood loss occurred during emergency (μ=780 ml) compared to elective Caesarean (μ=497 ml) or vaginal delivery (μ=422 ml). There was no significant difference in Apgar<5 or admission to neonatal unit between groups. Conclusion: Involving senior obstetricians in discussions with women regarding mode of delivery and active discouragement of Caesarean for non-medical reason, appears to increase VBAC rates.